Fabrication and characterization of pcl/ha/ppy composite scaffold using freeze-drying technique - Joseph Ufere, Sharon Kalu (Penerbit UTM Press, 2016)
Bone tissue regeneration and healing could be notably quickened via applying electrical stimuli in the defected area. Hence, a conductive tissue engineer ing sc affold that is capable of delivering the electrical stimuli is greatly desirable. In this study, electrically conductive sca ffold was fabricated by using a biocompatible conductive polymer, polypyrrole (PPY) in the optimized nanocomposite scaffold of Polyc aprolactone (PCL) and Hydroxyapatite (HA) using freeze – drying technique. The sc affolds were evaluated by using a number of techniques. The morphology of the scaffolds was observed and analyzed using a scanning electron microscope (SEM) . Composite scaffolds with suitable pore size distribution were obtained by freezing the polymer solution mixture at - 18ºC, by controlling the polymer and solvent phase crystallization. The result s showed that the average pore sizes were decreased from 123.7μm for PCL scaffolds to 91.6 μm with the incorporation of HA nanoparticles. Electrical conductivity of the scaffolds was evaluated using a digital multimeter. The wettab ility and porosity of the scaffolds were increase d with the incorporation of Polypy rrole than Polycaprolactone scaffold . The newly fabricated PCL/HA/PPY scaffold showed good prospect to be employed for bone tissue engineering applications.